Problem-Based Learning with Manipulative Media: Enhancing Elementary Students' Conceptual Understanding in Area and Volume - Dewanti, Sintha Sih; Rahmawati; Sumardi (Universitas Pendidikan Ganesha, 2024)
The learning model plays a crucial role in ensuring students' conceptual understanding through active and meaningful learning experiences. A structured and collaborative model fosters a conducive learning environment, encouraging students to actively grasp concepts. This study aims to develop a Problem-Based Learning (PBL) model assisted by manipulative media to enhance elementary students' conceptual understanding of area and volume measurement. The study follows a Research & Development approach using the ADDIE model, with fourth-grade elementary students as research subjects. Data collection techniques include interviews, classroom observations, and tests. The data were analyzed qualitatively using descriptive analysis. The findings reveal that students became more actively engaged in the learning process and were able to connect abstract concepts through hands-on practice using manipulative media. The independent learning activity level reached 91.84%, while group activities achieved 96.85% in the first session and 97.30% in the second session. The test results on area and volume measurement indicated a mastery learning rate of 96.76%. Students' conceptual understanding fell into the very high category, with a mastery percentage between 85-100% based on the Criterion-Referenced Assessment scale. The study concludes that implementing the PBL model assisted by manipulative media effectively enhances students' conceptual understanding and promotes their active participation in collaborative problem-solving activities.